Ant : the incredible journey of NBA rising star Anthony Edwards - Hine, Chris (Harper, an imprint of HarperCollins Publishers, 2025)
"The first in-depth look at the Minnesota Timberwolves rising star, from his backstory to his mindset, and the relationships that fueled his drive to greatness. From his jaw-dropping dunks to his charismatic personality, Anthony Edwards draws comparisons to the greatest shooting guards of all time like Kobe and Jordan. A portrait in the education of a budding NBA superstar, Ant chronicles Edward's meteoric rise. The number-one pick in the 2020 NBA Draft, a two-time All-Star, Edwards has, in just a few seasons, become a household name and the face of the Minnesota Timberwolves. And he's only twenty-three years old. With locker room access, original interviews, and fresh reporting by Chris Hine, the Minnesota Star Tribune's beat writer covering the Wolves, Ant delves into Edwards' early life in Atlanta, the challenges and family tragedy he overcame, and the relentless determination that has propelled him to stardom"--